ANALISIS KESULITAN SISWA SMP DALAM MENYELESAIKAN SOAL PADA MATERI ARITMETIKA SOSIAL - Yuni Sapitri; Nelly Fitriani; Gida Kadarisma (IKIP Siliwangi, 2020)
This study aims to find out the difficulties of junior high school students in working on descriptive questions on social arithmetic material and to analyze the factors. The subjects of this study were 26 students of class VIII SMP Buana Panca Bakti Cianjur totaling 26 people in the 2019-2020 school year. Data collection in this study was conducted by means of tests, interviews and documentation. Before the interview, a math test was conducted with 5 questions of social arithmetic material. After the tests and interviews are carried out, the results of the tests and interviews are analyzed and taken from the difficulties the students experience when working on social arithmetic questions. The data analysis techniques used in this study were: (1) data reduction, by selecting the main things and focusing the important things, (2) data presentation, presenting the data on student work, (3) drawing conclusions. The results showed that the students' difficulties when solving social arithmetic problems were difficulties in understanding the problems because social arithmetic problems were in the form of story problems, difficulties in mathematical models and difficulties in the process or steps of completion. The factors that cause students' difficulties because students are lazy to read the questions, it is difficult to digest the words and the meaning of the questions, students are less interested in learning mathematics, and students do not understand the arithmetic operation well.